Physicochemical quality parameters, antibacterial properties and cellular antioxidant activity of Polish buckwheat honey. (April 2020) - Dżugan, Małgorzata; Grabek-Lejko, Dorota; Swacha, Sylwia; Tomczyk, Monika; Bednarska, Sabina; Kapusta, Ireneusz
Abstract: Buckwheat honey is the darkest Polish honey and has the strongest antibacterial and antioxidant activity; however, the mechanism of this bioactivity remains unknown. To determine the factors responsible for the bioactivity of buckwheat honey, antioxidant power, radical scavenging activity, and total phenolic and flavonoid contents of 20 buckwheat honey samples from southeastern Poland were measured. The antibacterial activity of the honey was studied using 4 bacterial strains. The effect of catalase on the antibacterial action of the honey was determined. Five buckwheat honey samples with different antioxidant and antibacterial activities were selected, and their phenolic profiles were characterized in detail with UPLC-PDA-MS/MS. In vivo experiments showed that these samples protected cells of the yeast Saccharomyces cerevisiae exposed to hydrogen peroxide, which was used as a hydroxyl radical generator. The antibacterial activity was significantly correlated with antioxidant activity and phenolic compounds (p < 0.05). The removal of H2 O2 by catalase partially eliminated (30–50%) the bacteriostatic activity of the honeys. The results indicated that among the 13 phenolic compounds identified in buckwheat honeys, only quercetin, rutin, chlorogenic acid and caffeic acid were correlated with its antioxidative and antibacterial activity, which was shown by using Principal Component Analysis (PCA). The protective effect of buckwheat honey resulting from its polyphenols content was confirmed (p < 0.05) against in situ -generated hydroxyl radicals using the S. cerevisiae yeast cells as a biological model.